Impaired sensitivity to thyroid hormones is associated with ASCVD risk factors in Beijing in euthyroid population: a cross-sectional study - Shi, Lintao; Wang, Jianjun; Yang, Li; Zhao, Weichao; Zhang, Min; Yu, Aiyun; Ni, Lingfang; Liu, Yu; Jia, Haiying (Frontiers in Endocrinology, 2025)
BackgroundThis review aims to investigate the relationship between impaired sensitivity to thyroid hormones and ASCVD risk factors in the euthyroid population.MethodsA cross-sectional study including 7,895 euthyroid subjects aged ≥18 years old was conducted. Height, body weight, blood pressure (BP) were measured, and serum concentrations of lipids, fasting blood glucose, uric acid, free thyroxine (FT4), free triiodothyronine (FT3), and thyrotropin (TSH) were assayed. Thyroid hormone resistance was calculated by Thyroid-stimulating hormone (TSHI), Thyroid Feedback Quantile-based Index (TFQI), and Free Triiodothyronine/Free thyroxine (FT3/FT4), which were calculated based on FT3, FT4, and TSH.ResultsWe are divided into four groups according to the TFQI quartile. Age, BMI, BP, HDL-C, TC, TG, FBG, UA were statistically significant between the four groups. F3/F4 showed statistical significance in populations with high UA, high FBG, and high TG; TFQI was positively correlated with BP, TG, FBG, UA and TyG, SBP, FBG, UA and TyG, FT3/FT4 was negatively correlated with DBP, SBP, TC, TG and UA.ConclusionImpaired sensitivity to thyroid hormone in euthyroid population is associated with ASCVD risk factors. These findings are potentially useful for understanding the interaction between thyroid hormone sensitivity and ASCVD risk factors in euthyroid population.